2011
DOI: 10.3758/s13423-011-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Haptic experiences influence visually acquired memories: Reference frames during multimodal spatial learning

Abstract: In two experiments, we investigated whether reference frames acquired through touch could influence memories for locations learned through vision. Participants learned two objects through touch, and haptic egocentric (Experiment 1) and environmental (Experiment 2) cues encouraged selection of a specific reference frame. Participants later learned eight new objects through vision. Haptic cues were manipulated, whereas visual learning was held constant in order to observe any potential influence of the hapticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…There are indications that visual and haptic perception are processed dependently [9] and that vision and haptics share common abstract representations of the shape and structure of objects [3]. Furthermore it has been shown that spatial layouts, which were learned through haptic and visual exploration, are stored within a common reference frame: Haptic experiences were able to influence memories that were acquired visually [8]. Previous studies also revealed that physical objects were recalled more frequently than pictures, and pictures more often than words [2].…”
mentioning
confidence: 95%
“…There are indications that visual and haptic perception are processed dependently [9] and that vision and haptics share common abstract representations of the shape and structure of objects [3]. Furthermore it has been shown that spatial layouts, which were learned through haptic and visual exploration, are stored within a common reference frame: Haptic experiences were able to influence memories that were acquired visually [8]. Previous studies also revealed that physical objects were recalled more frequently than pictures, and pictures more often than words [2].…”
mentioning
confidence: 95%
“…structure of the layout (e.g., Mou & McNamara, 2002), the presence of environmental structure (e.g., Kelly, Avraamides, & Giudice, 2011), and experimental instructions (Greenauer & Waller, 2008). In fact, people weigh multiple cues that are available at the time of encoding, in order to select a reference frame .…”
mentioning
confidence: 99%
“…People also show equivalent performance across source modalities when making judgments of relative direction from imagined perspectives (Avraamides, Loomis, Klatzky & Golledge, 2004;Giudice et al, 2009;Kelly, Avraamides, & Giudice, 2011).…”
Section: The Spatial Imagementioning
confidence: 85%